2015
DOI: 10.1007/s11999-014-4009-8
|View full text |Cite
|
Sign up to set email alerts
|

What Are the Functional Results and Complications From Allograft Reconstruction After Partial Hemipelvectomy of the Pubis?

Abstract: Background In patients undergoing hemipelvectomies including resection either of a portion of the pubis or the entire pubis from the symphysis to the lateral margin of the obturator foramen while sparing the hip (so-called Dunham Type III hemipelvectomies), reconstructions typically are not performed given the preserved continuity of the weightbearing axis and the potential complications associated with reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 17 publications
0
18
0
1
Order By: Relevance
“…For the treatment of bone defects after type III hemipelvectomy, more and more surgeons tend to reconstruct defect because of the reported complications. Up to now, allograft, mesh repair and arti cial ligament repair are the main choices for reconstruction after type III hemipelvectomy (11,12,16). Recent reconstruction ways after type III resection were listed in Table 3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the treatment of bone defects after type III hemipelvectomy, more and more surgeons tend to reconstruct defect because of the reported complications. Up to now, allograft, mesh repair and arti cial ligament repair are the main choices for reconstruction after type III hemipelvectomy (11,12,16). Recent reconstruction ways after type III resection were listed in Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, some reconstruction methods have been reported after type III hemipelvectomy, including allograft, mesh and arti cial ligament (11,12). However, large amount of studies revealed various limitations of these reconstruction options.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, allograft, mesh, and artificial ligament are the most common reconstruction methods after type III resection [11,12]. Although allograft could provide a bony reconstruction, high operative infection rate was frequently reported by some researches [2].…”
Section: Introductionmentioning
confidence: 99%
“…Although allograft could provide a bony reconstruction, high operative infection rate was frequently reported by some researches [2]. Researches showed that the infection rate of allograft after type III internal hemipelvectomy is as high as 20% [11,13]. Soft tissue reconstruction like mesh and the artificial ligament is easy and convenient, but the mechanical stability of the pelvis is ignored which results in changes of pelvic structure and mechanics causing complications like acetabular shift and sacroiliitis.…”
Section: Introductionmentioning
confidence: 99%